Age of ovarian cancer diagnosis among BRIP1, RAD51C, and RAD51D mutation carriers identified through multi-gene panel testing - Shelly Cummings; Susana San Roman; Jennifer Saam; Ryan Bernhisel; Krystal Brown; Johnathan M. Lancaster; Lydia Usha (BMC, 2021)
Abstract Background Professional society guidelines recommend risk-reducing salpingo-oophorectomy (RRSO) for women with pathogenic variants (PVs) in ovarian cancer-risk genes. Personalization of that intervention is based on gene-specific phenotypes; however, the age of ovarian cancer diagnosis in women with PVs in moderate penetrance ovarian cancer-risk genes is not well characterized. Women who had hereditary cancer panel testing from September 2013-May 2019 were included (N = 631,950). Clinical/demographic information was compared for women with a PV in BRIP1, RAD51C, or RAD51D versus in BRCA1 or BRCA2. Results PVs in BRIP1, RAD51C, or RAD51D were identified in 0.5% of all tested women but in 1.6% of women with a history of ovarian cancer (~ 3-fold increase). PVs in BRCA1 or BRCA2 were identified in 2.4% of all tested women but in 6.1% of women with a history of ovarian cancer (~ 2.5-fold increase). The proportion of women with a personal or family history of ovarian cancer was similar among women with a PV in BRIP1, RAD51C, RAD51D, BRCA1, or BRCA2. The median age at ovarian cancer diagnosis was 53 years for BRCA1, 59 years for BRCA2, 65 years for BRIP1, 62 years for RAD51C, and 57 years for RAD51D. Conclusions These data reinforce the importance of identifying PVs in moderate penetrance ovarian cancer-risk genes. The age at ovarian cancer diagnosis was older for women with PVs in BRIP1, RAD51C, or RAD51D, suggesting that it is safe to delay RRSO until age 45-50 in RAD51D PV carriers and possibly until age 50-55 in BRIP and RAD51C PV carriers.